Genomic mechanisms for cold tolerance and production of exopolysaccharides in the Arctic cyanobacterium Phormidesmis priestleyi BC1401 - Chrismas, Nathan; Barker, Gary; Anesio, Alexandre; Sรกnchez-Baracaldo, Patricia (Figshare, 2016)
Abstract Background Cyanobacteria are major primary producers in extreme cold ecosystems. Many lineages of cyanobacteria thrive in these harsh environments, but it is not fully understood how they survive in these conditions and whether they have evolved specific mechanisms of cold adaptation. Phormidesmis priestleyi is a cyanobacterium found throughout the cold biosphere (Arctic, Antarctic and alpine habitats). Genome sequencing of P. priestleyi BC1401, an isolate from a cryoconite hole on the Greenland Ice Sheet, has allowed for the examination of genes involved in cold shock response and production of extracellular polymeric substances (EPS). EPSs likely enable cyanobacteria to buffer the effects of extreme cold and by identifying mechanisms for EPS production in P. priestleyi BC1401 this study lays the way for investigating transcription and regulation of EPS production in an ecologically important cold tolerant cyanobacterium. Results We sequenced the draft genome of P. priestleyi BC1401 and implemented a new de Bruijn graph visualisation approach combined with BLAST analysis to separate cyanobacterial contigs from a simple metagenome generated from non-axenic cultures. Comparison of known cold adaptation genes in P. priestleyi BC1401 with three relatives from other environments revealed no clear differences between lineages. Genes involved in EPS biosynthesis were identified from the Wzy- and ABC-dependent pathways. The numbers of genes involved in cell wall and membrane biogenesis in P. priestleyi BC1401 were typical relative to the genome size. A gene cluster implicated in biofilm formation was found homologous to the Wps system, although the intracellular signalling pathways by which this could be regulated remain unclear. Conclusions Results show that the genomic characteristics and complement of known cold shock genes in P. priestleyi BC1401 are comparable to related lineages from a wide variety of habitats, although as yet uncharacterised cold shock genes in this organism may still exist. EPS production by P. priestleyi BC1401 likely contributes to its ability to survive efficiently in cold environments, yet this mechanism is widely distributed throughout the cyanobacterial phylum. Discovering how these EPS related mechanisms are regulated may help explain why P. priestleyi BC1401 is so successful in cold environments where related lineages are not.